Jogos eletrônicos na educação física: possibilidades para escolas com poucos recursos digitais - Lourenço, Elker de Oliveira (2023)
Electronic Games have increasingly become part of the lives of many children and adolescents who are of school age. In addition, national and state curriculum documents already bring these games as content to be studied in Physical Education classes at school. Therefore, the school can contribute to the mediation between students and this type of game. However, many school units do not have digital resources to offer experiences with these games. Based on this reality, the general objective of the research was to identify, develop and analyze possibilities for teaching Electronic Games in Physical Education at school, articulated with the principles of Media-education, considering the school realities that have few digital resources. The research adopted, in the methodological aspect, the qualitative approach. It was oriented from action research principles and was developed in a municipal public school in the city of Aparecida de Goiânia - GO. Participating in the research were Physical Education teachers who belong to the same teaching network and students from a 5th grade class of Elementary School. For data collection, the following were used: a questionnaire answered by the teachers; two questionnaires (initial and final) answered by the students and a Field Diary to record data from the seventeen classes that made up the intervention applied at the school. This intervention was carried out from a pedagogical sequence produced for this research. The results obtained in the study indicate that the insertion of Electronic Games in the school can contribute to the enjoyment of students with these games, help in the creation and learning of students, promote discussions about the evolution of technologies and provide the problematization of social issues that are related directly or indirectly with these games. Finally, it is considered that the research was able to point out possibilities of how to work with Electronic Games, even in school realities that have few technological resources available. Despite this, it is argued that it is up to the State to provide more digital resources to work with these games in schools, in addition to offering continuing education for teachers, so that the possibilities of working with Electronic Games in Physical Education at school can be improved, even more expanded. This research also gave rise to two Educational Products, one being an ebook entitled "ELECTRONIC GAMES AND MEDIA-EDUCATION: Pedagogical Possibilities for Physical Education at School ", and a video presentation that aimed to give visibility to the experiences lived in the pedagogical intervention. Both products will be made available online and free of charge.